11: OBSERVATIONS ON MOVEMENT, BEHAVIOR, AND DEVELOPMENT OF TURKEY BROODS* - Lovett E. Williams Jr.; David H. Austin; Tommie E. Peoples; Robert W. Phillips (Wildlife Society Bulletin)
ABSTRACT Twelve broods of wild turkeys (Meleagris gallopavo osceola) were studied in southern Florida with radio‐tracking techniques. Hens used an ecotone between grassy pasturelike areas and denser scrub for nesting. After the broods hatched, they went directly into cypress (Taxodium distichum) woods and remained there for at least the first 4 weeks of life. The loss of some very young poults coincided with the time that the broods crossed streams or other surface water, but no loss was known to have resulted from falling rain. Some flightless poults could swim well. Each newly hatched brood left its nest at a different time of day, but none departed within 2 hours of sunrise or sunset. Broods roosted in different places on the ground each night for the first 12 or 13 nights. Afterwards they roosted in trees. Poults could fly well at least 1 or 2 days before they began roosting in trees. Brood hens covered ground‐roosting poults with their bodies, outspread wings, and partly spread tail feathers. For at least 4 weeks after they began roosting in trees, some of the poults were sheltered by the hen's outspread wings. Turkey hens often revealed by their behavior that they were aware of the exact moment that they were spotted by observers. Data on movement and on habitat utilization of young broods, behavior of broods and brood hens when disturbed, and other observations on the life history of turkeys through about 8 weeks of age are presented.